Silent sinus syndrome: an unusual case of facial numbness. Issue 6 (20th July 2018) - Tribich, Samuel; Mahoney, Colin J; Davies, Nicholas W
Abstract : A 49-year-old man presented with a 1-week history of right facial paraesthesia with blurred vision and diplopia. Examination was normal apart from reduced facial sensation. Following appropriate neuroimaging, we considered a diagnosis of silent sinus syndrome. He underwent a middle meatal antrostomy with complete resolution of symptoms. Silent sinus syndrome results from occlusion of the osteomeatal complex, preventing normal aeration of the maxillary sinus. Maxillary sinus hypoventilation typically causes inferior displacement of the globe in the orbit (unilateral hypoglobus). Neurologists will only infrequently see people with silent sinus syndrome but it can have devastating consequences if left untreated and so must be considered in the appropriate clinical context.